2014
DOI: 10.1002/2013jd020838
|View full text |Cite
|
Sign up to set email alerts
|

Roles of transport and chemistry processes in global ozone change on interannual and multidecadal time scales

Abstract: This study investigates ozone changes and the individual impacts of transport and chemistry on those changes. We specifically examine (1) variation related to El Niño Southern Oscillation, which is a dominant mode of interannual variation of tropospheric ozone, and (2) long‐term change between the 2000s and 2100s. During El Niño, the simulated ozone shows an increase (1 ppbv/K) over Indonesia, a decrease (2–10 ppbv/K) over the eastern Pacific in the tropical troposphere, and an increase (50 ppbv/K) over the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 102 publications
(112 reference statements)
2
30
0
Order By: Relevance
“…ENSO has been shown to modulate the tropospheric ozone burden across the tropical Pacific Ocean with lower tropospheric column ozone corresponding to the cloudiest regions (Ziemke and Chandra, 2003;Sekiya and Sudo, 2014). Zeng and Pyle (2005) calculated an anomalously large increase in stratosphere-troposphere exchange following a typical El Niño year, increasing the global tropospheric ozone burden.…”
Section: Climate Variabilitymentioning
confidence: 99%
“…ENSO has been shown to modulate the tropospheric ozone burden across the tropical Pacific Ocean with lower tropospheric column ozone corresponding to the cloudiest regions (Ziemke and Chandra, 2003;Sekiya and Sudo, 2014). Zeng and Pyle (2005) calculated an anomalously large increase in stratosphere-troposphere exchange following a typical El Niño year, increasing the global tropospheric ozone burden.…”
Section: Climate Variabilitymentioning
confidence: 99%
“…therein). A few studies show that CCMs driven by observed SSTs (AMIP mode; see Section 2.1) are able to capture the overall pattern and magnitude of the tropical ozone response to ENSO obtained from satellite measurements (Oman et al, 2013;Sekiya and Sudo, 2014), including the observed ozone-ENSO index (Ziemke et al, 2010;Oman et al, 2011). This is calculated as the difference between observed monthly mean column ozone over two broad regions in the western and eastern Pacific ocean; see Figure 8 for an example.…”
Section: State Of Knowledgementioning
confidence: 99%
“…Because our interest is to study how meteorology influences the interannual variation of ozone transport from North America to East Asia, we allow the meteorology to vary from year to year between 1987 and 2006 but keep the chemistry the same for all years, i.e., we use the archived daily ozone production and loss data in 2005 for all years (year 2005 was randomly chosen). This is an effective approach that has also been used in previous studies (Li et al, ; Liu et al, ; Liu et al, ; Sekiya & Sudo, ). Therefore, the interannual variability of the NA ozone presented in section 5 is driven by meteorology only, while the seasonality of the GEOS‐Chem simulations presented in section 4 is the result of the combined effects of meteorology and chemistry.…”
Section: Model and Datamentioning
confidence: 99%